IMPLEMENTASI AKAD MURABAHAH DI PERBANKAN SYARIAH KOTA PADANGSIDIMPUAN - Puji Kurniawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
Sharia Bank is one of the financial institutions as an intermediary for financial services in Indonesia, this is recorded in the Law of the Republic of Indonesia Number 7 of 1992 concerning Banking, Law of the Republic of Indonesia Number 10 concerning Amendments to Law Number 7 of 1998 concerning Banking, Law of the Republic of Indonesia Number 3 of 2004 concerning Amendment to Law of the Republic of Indonesia Number 23 of 1999 concerning Bank Indonesia, Law of the Republic of Indonesia Number 3 of 2006 concerning Amendment to Law of the Republic of Indonesia Number 7 of 1989 concerning Religious Courts. All of these regulations are the place to implement the mudarabah agreement in Padangsidimpuan City, which I will describe in the discussion below.